Evaluating the knowledge ability of students by inquiry-based learning technique - Wesam Salah Alaloul; Khalid Mhmoud Alzu’bi; Muhammad Ali Musarat (International Journal of Evaluation and Research in Education (IJERE), 2026)
Inquiry-based learning (IBL) as an instructional approach has been popular amongst science, technology, engineering, mathematics disciplines, but the practice specifically in engineering education deserves further exploration. This study explores the impact of IBL on student engagement and learning within an engineering project management course. Using a case-study methodology, engineering students engaged in real-world problem-solving activities and provided feedback through a questionnaire assessing lecturer deliverables and IBL effectiveness. For this study, a questionnaire approach was adopted comprised of 34 questions compressed under two main groups. The distribution was made among engineering students of various disciplines. The descriptive and reliability analysis of the responses revealed that IBL positively influenced students’ engagement and problem-solving abilities, fostering a collaborative learning environment. However, students noted a high workload associated with IBL tasks, suggesting the need for careful assignment structuring. Overall, the study highlights IBL’s potential to enrich engineering education by aligning learning outcomes with industry demands, recommending that future implementations consider workload optimization to maintain balance. This research contributes to understanding effective pedagogical approaches in engineering, promoting student-centered learning that prepares students for professional challenges.